Does it matter who places the intravenous? An inter-professional comparison of prehospital intravenous access difficulties between physicians and paramedics - Prottengeier, Johannes; Maier, Jan-Niklas; Gall, Christine; Heinrich, Sebastian; Schmidt, Joachim; Birkholz, Torsten (European Journal of Emergency Medicine, 2016)
Depending on the specific national emergency medical systems, venous cannulations may be performed by physicians, paramedics or both alike. Difficulties in the establishment of vascular access can lead to delayed treatment and transport. Our study investigates possible inter-professional differences in the difficulties of prehospital venous cannulation.Paramedics were interviewed for their personal attitudes towards and experiences in venous access. We analysed 47 candidate predictor variables in terms of cannulation failure and exceedance of a 2 min time threshold. Multivariable logistic regression models were fitted for variables of potential predictive value (P<0.25) and evaluated by the area under the curve (AUC>0.60) of their respective receiver operating characteristic curve. Results were compared with previously published data from emergency physicians.A total of 552 cannulations were included in our study. All 146 participants voted that paramedics should be eligible to perform venous catheterizations. Despite ample experience in the task, almost half of them considered prehospital venous cannulations more difficult than those performed in hospital. However, the multivariable logistic regression found only patient-related and puncture site factors to be predictive of cannulation failure (patient age, vein palpability with tourniquet, insufficient ambient lighting: model AUC: 0.72) or cannulation delay (vein palpability with tourniquet: model AUC: 0.60).Our study shows that venous cannulation is well established among paramedics. It presents itself with similar difficulties across medical professions. Not the numerous specific circumstances of prehospital emergency care, but universal factors inherent to the task will influence the success at venous catheterization.
EVALuna2:16736